2013
DOI: 10.2209/tdcpublication.54.117
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate-related Osteonecrosis of Jaw (BRONJ) in Japanese Population: A Case Series of 13 Patients at Our Clinic

Abstract: Bisphosphonate-related osteonecrosis of the jaw (BRONJ) affects quality of life and is an important problem for dentists. A Japanese position paper on BRONJ was published in 2010. The purpose of this study was to review clinical data on the treatment of BRONJ obtained at the Clinic of Oral and Maxillofacial Surgery, Tokyo Dental College, Chiba Hospital to further our understanding of this disease. A total of 13 patients (6 men and 7 women) were included. All the patients included in this study had received Bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…Nomura reported two female Japanese patients with RA with ONJ, and both were over 70 years of age and were taking glucocorticoids [8]. Our study confirms these clinical characteristics [7,8] in our Japanese patients with RA. Our data suggest that Japanese rheumatologists and dentists may stop treatment with bisphosphonates before tooth extraction, and recognize patients with RA as being at high risk of ONJ if they are elderly woman who are glucocorticoid users and have comorbid diseases like diabetes.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Nomura reported two female Japanese patients with RA with ONJ, and both were over 70 years of age and were taking glucocorticoids [8]. Our study confirms these clinical characteristics [7,8] in our Japanese patients with RA. Our data suggest that Japanese rheumatologists and dentists may stop treatment with bisphosphonates before tooth extraction, and recognize patients with RA as being at high risk of ONJ if they are elderly woman who are glucocorticoid users and have comorbid diseases like diabetes.…”
Section: Discussionsupporting
confidence: 86%
“…Conte-Neto and colleagues reported that patients with RA who develop ONJ are usually women over the age of 60 years who are taking steroids and receiving long-term bisphosphonate therapy [7]. Nomura reported two female Japanese patients with RA with ONJ, and both were over 70 years of age and were taking glucocorticoids [8]. Our study confirms these clinical characteristics [7,8] in our Japanese patients with RA.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations